2006
DOI: 10.1111/j.1075-122x.2006.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Musculus Sternalis: A Normal but Rare Mammographic Finding and Magnetic Resonance Imaging Demonstration

Abstract: A spiculated triangular opacity with irregular contours was detected in the craniocaudal screening mammogram of a 47-year-old woman with positive family history of breast carcinoma (Fig. 1). Magnetic resonance imaging (MRI) demonstrated sternal muscle paralleling the pectoralis muscle (Fig. 2).Bilateral lobulated heterogeneous opacities containing fatty tissue, were detected on the medial quadrants of the craniocaudal mammograms of a 50-year-old woman undergoing mammographic screening (Fig. 3). MRI revealed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The sternalis muscle, when present appears as a flame shaped or speculated triangular structure on the medial aspect of craniocaudal projections [23]. Identification and recognition of this rare anatomical variant can reduce the chances of misdiagnosis, avoid subsequent diagnostic procedures like biopsies, and also misinterpretation as recurrence at a later date [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sternalis muscle, when present appears as a flame shaped or speculated triangular structure on the medial aspect of craniocaudal projections [23]. Identification and recognition of this rare anatomical variant can reduce the chances of misdiagnosis, avoid subsequent diagnostic procedures like biopsies, and also misinterpretation as recurrence at a later date [4].…”
Section: Discussionmentioning
confidence: 99%
“…Identification and recognition of this rare anatomical variant can reduce the chances of misdiagnosis, avoid subsequent diagnostic procedures like biopsies, and also misinterpretation as recurrence at a later date [4]. Sternalis muscle when present can mimic a focal density and its presence can be confirmed by MRI or CT imaging [23].…”
Section: Discussionmentioning
confidence: 99%
“…SM has been discovered on mammography, magnetic resonance imaging (MRI), and computed tomography (CT). Bradley et al (1996) found 4 cases out of an estimated 32000 mammograms that gave signals at the position of SM while Goktan et al (2006) and Nuthakki et al (2007) identified SM cases using mammography and MRI. Young Lee et al (2006) encountered 86 cases out of 1387 CT chest scans where 7.3% of the cases were female, and 5.3% were male.…”
Section: Discussionmentioning
confidence: 99%
“…The muscle is isodense with fibroglandular densities and can be seen with varying diameters, shapes and contours on mammograms (9). The obtuse angle at the chest wall is typical of a muscular structure, and it is usually surrounded by fat (10).…”
Section: Discussionmentioning
confidence: 99%